Development of Programmable Logic Controller (PLC) Trainer Learning Media for Industrial Automation - Widinata, Fandi; Wirawan, I Made (research, training and philanthropy institution Natural Aceh, 2025)
This research aims to develop learning media through PLC trainers and job sheets to support practical learning in the subject of Programmed Control Systems at Vocational High School (SMK) Negeri 1 Singosari. The background of this research is the limited real practice media, where students previously only relied on simulations, causing a gap between understanding theory and practical skills. The development model used in this research follows the ADDIE framework, which consists of five stages: Analysis, Design, Development, Implementation, and Evaluation. Data was collected through interviews, observations, expert validation, and user trials involving 11th-grade students of Industrial Automation Engineering of SMK Negeri 1 Singosari. The results showed that the trainer and jobsheet developed were declared